Growth of the Patagonian Andessince the Mid Jurassic to the Present - Folguera Telichevsky, Andres (2018)
The Patagonian Andes have been constructed through several deformational stages. Thus, Jurassic within plate contractional associated with a stable seismic ridge impacting at the Patagonian trench. These Cretaceous contractional structures are affectedby Eocene deformations that are variable in mechanics depending on the latitude: While some segments of the fold and thrustbelt are extensionally reactivated, others are contractionally reactivated. This variable behavior is interpreted as due to the obliquecollision of a seismic ridge from north to south that produced slab windows alternated with segments where transform segments the outstanding detachment of Los Chonos fore-arc sliver. This extensional stage ends at the earliest Miocene with Atlantic and fold and thrust belt that reaches Central Patagonia in mid-Miocene times. This process is accompanied by mild east-ward arcmigrations at the edges of the Chonos accretion zone interpreted as subducted slab shallowing. Late Miocene deformation isfocused on out-of-sequence thrusts that produce the rain shadow conditions that characterize Patagonia producing strong biotachanges. Mild Quaternary reactivations of the Miocene systems are the late expression of this uplift.